Plant provenance affects pollinator network: Implications for ecological restoration. Issue 2 (21st April 2021) - Bucharova, Anna; Lampei, Christian; Conrady, Malte; May, Emilia; Matheja, Janis; Meyer, Michael; Ott, David
Abstract: The selection of plant provenance for ecological restoration is an intensively debated topic. Throughout this debate, arguments mostly focus on plant performance, but little attention is paid to the effects of provenance on other members of the restored ecosystem. On the other hand, in restoration projects that focus specifically on supporting interacting biota, for example, wildflower strips among fields to support pollinators, the provenance choice is often not considered, partly because the effect of provenance on pollinators is unknown. In this pioneering case study, we tested whether pollinators differentiate between experimental plant communities of different provenances. We established experimental plant communities with the same species composition but with plants originating from three different provenances. We then recorded plant phenology and observed pollinators and flower visitors interacting with these experimental communities and related the pollinator visitation to the provenance identity. The provenances of the experimental plant communities had a strong and significant effect on the diversity and abundance of flower–pollinator interactions, with one provenance interacting two times as often as the other two provenances. The effect was driven by the differences in flowering phenology among provenances. Synthesis and applications . Plant provenances substantially differ in their interactions with local pollinators. Therefore, the selection of plant provenance should be considered when planning restoration projects for the support of pollinators. Abstract : Plant provenances substantially differ in their interactions with local pollinators. Therefore, the selection of plant provenance should be considered when planning restoration projects for the support of pollinators. Abstract: Die richtige Auswahl der Herkunft von Pflanzen für die ökologische Renaturierung ist ein intensiv diskutiertes Thema. In dieser Debatte liegt der Fokus in erster Linie auf der Performance der Pflanzen. Weit weniger Aufmerksamkeit erhält die Auswirkung der Herkunft auf andere Mitglieder des wiederhergestellten Ökosystems. In Renaturierungsprojekten, wiederum, die sich speziell auf die Unterstützung interagierender Biota konzentrieren, z.B. Blühstreifen zwischen Feldern zur Unterstützung von Bestäubern, wird die Wahl der Herkunft der Pflanzen häufig nicht berücksichtigt. Dies ist teilweise darauf zurückzuführen, dass die Wirkung der Herkunft auf Bestäuber unbekannt ist. In dieser wegbereitenden Fallstudie testeten wir, ob Bestäuber zwischen experimentellen Pflanzengemeinschaften verschiedener Provenienzen unterscheiden. Wir etablierten experimentelle Pflanzengemeinschaften mit der gleichen Artenzusammensetzung, aber mit Pflanzen aus drei verschiedenen Herkünften. Anschließend erfassten wir die Phänologie der Pflanzen, beobachteten Bestäuber und Blütenbesucher, die mit diesen experimentellen Gemeinschaften interagierten, und setzten den Besuch der Bestäuber mit der Herkunft der Pflanzen in Beziehung. Die Herkünfte der experimentellen Pflanzengemeinschaften hatten einen starken und signifikanten Einfluss auf die Vielfalt und Häufigkeit von Blüten‐Bestäuber‐Interaktionen, wobei eine Herkunft doppelt so häufig besucht wurde wie die anderen beiden. Dieser Effekt wurde durch die Unterschiede in der Blühphänologie zwischen den Herkünften hervorgerufen. Synthese und Anwendungen . Pflanzenherkünfte unterscheiden sich erheblich in ihren Interaktionen mit lokalen Bestäubern. Daher sollte bei der Planung von Renaturierungsprojekten zur Unterstützung von Bestäubern die Auswahl des Herkunftsortes der Pflanzen berücksichtigt werden.